An Analysis of Students’ Learning Motivation in Pancasila Education Based on Six Dimensions - Rahmia Tulljanah; Rulian Zahratul Fatiha; Annisa Kharisma; Yoga Suhendra; Kurniati Ramadhini (International Journal of Elementary School, 2026)
This study describes the profile of elementary students’ learning motivation in Pancasila Education based on six dimensions proposed by Uno (2021): the desire to succeed, the drive and need for learning, future aspirations, interesting learning activities, a conducive learning environment, and learning appreciation. A quantitative descriptive approach was employed involving 47 fifth-grade students selected through purposive sampling from a population of 69 students. Data were collected using a 20-item closed-ended Likert-scale questionnaire developed based on the six dimensions and supported by structured classroom observations of students’ attention, interest, participation, and persistence. The instrument demonstrated high content validity (90%) and reliability (Cronbach’s Alpha = 0.926). Data were analyzed descriptively using percentage categorization, while an independent-samples t-test was used as a supplementary analysis to compare motivation under two naturally occurring instructional conditions. The results showed that overall learning motivation was categorized as very high (12.77%), high (42.55%), moderate (34.04%), and low (10.64%), with no students classified as having very low motivation. The desire to succeed and interesting learning activities emerged as the strongest dimensions, whereas future aspirations and a conducive learning environment were relatively less developed. The findings indicate that varied and engaging learning activities can support multiple dimensions of students’ learning motivation. Teachers are therefore encouraged to implement varied, contextual, and appreciative learning activities to strengthen students’ motivation in Pancasila Education.